2023
DOI: 10.1039/d3ea00058c
|View full text |Cite
|
Sign up to set email alerts
|

Case study evaluation of size-resolved molecular composition and phase state of carbonaceous particles in wildfire influenced smoke from the Pacific Northwest

Gregory W. Vandergrift,
Nurun Nahar Lata,
Susan Mathai
et al.

Abstract: Wildfires are significant sources of carbonaceous particles in the atmosphere. Given the dependence of atmospheric processes on particle physical and molecular properties, the interplay between particle size, phase state and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…, not commonly detected across all days) are shaded grey. Given the untargeted nature of this study and consequent lack of quantitative information, presence/absence of MFs are used to compare molecular coverage between days as similarly done in previous atmospheric studies with mass spectrometry application. ,,, While this strategy does not reveal what is occurring wholistically during an individual sampling event, it highlights the distinctive characteristics of that event relative to the rest of the sampling period. Here, only 291 MFs (13% by number) were found to be common across all daytime samples, indicating a high variability of MFs across all sampling days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, not commonly detected across all days) are shaded grey. Given the untargeted nature of this study and consequent lack of quantitative information, presence/absence of MFs are used to compare molecular coverage between days as similarly done in previous atmospheric studies with mass spectrometry application. ,,, While this strategy does not reveal what is occurring wholistically during an individual sampling event, it highlights the distinctive characteristics of that event relative to the rest of the sampling period. Here, only 291 MFs (13% by number) were found to be common across all daytime samples, indicating a high variability of MFs across all sampling days.…”
Section: Resultsmentioning
confidence: 99%
“…Nanospray desorption electrospray ionization (nano-DESI) was used to directly interface aerosol sampling with high resolution mass spectrometry (HRMS). The design and implementation of nano-DESI is based upon previous work. , While solid-phase extraction was initially explored as part of method development to minimize matrix effects, the minimal particle loadings necessitated the increased sensitivity afforded by direct nano-DESI analyses. Nano-DESI interfaces have also previously been shown to advantageously preserve oligomers and exhibit comparative resistance to matrix effects. ,, Briefly, the nano-DESI apparatus allows for direct, sensitive, in situ sampling of atmospheric particles impacted onto a substrate ( i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Smoke particles are characterized by a complex composition, including solid (e.g., black carbon) and liquid/oil-like organic phases (e.g., SVOCs). Some studies reported an increase in a liquid-like character for smaller particles [75,81]. The dynamics of the liquid and solid particle filtration differ significantly due to the differences in deposition modes (dendritic structures formed by solid particles vs. film formation by liquids), collision kinetics, and differences in the particle/fiber surface interactions.…”
Section: Characterization Of Initial Filtration Efficiency Of Pine Ne...mentioning
confidence: 99%